Fiber Bragg Grating Gap Sensor as An Innovative Idea for Critical Flange Monitoring - Mohd Hafizi, Zohari (Faculty of Mechanical & Automotive Engineering Technology, 2022)
Bolted joint integrity is a critical parameter to preserve for safe and efficient operation of the pipeline system, mainly in the flange gap monitoring exercise. Failure to precisely monitor any early signs of components gaping may result in a sudden failure or even injuries to personnel (Figure 1).